Accumulation by Dispossession and Socio-Environmental Conflicts Caused by the Expansion of Agribusiness in Argentina - Caceres, Daniel Mario (2015)
Drawing upon the concept of 'accumulation by dispossession', this paper analyses the expansion of agrarian capital in Argentina. A case study illustrates the social and environmental impacts of the expansion of agribusiness in central Argentina and the social struggle - both rural and urban - that has arisen to resist this process. Although government policies after the 2001 crisis differ in many ways from those of the 1990s, current agrarian policies are not significantly distinct from those followed during the pre-crisis neoliberal period. Rather than 'post-neoliberal', the new model could thus be better described as 'neo-extractivist'. With the connivance of the state, agribusiness is producing the largest-ever transformation of natural capital into economic capital in the history of the region. Moreover, the latest policy developments suggest that Argentina is on the threshold of a new and deeper stage of agrarian capital expansion and wealth concentration, this time operating at a much larger scale.